Transition temperature range of thermally activated nickel-titanium archwires - Tatiana Sobottka SPINI; Fabrício Pinelli VALARELLI; Rodrigo Hermont CANÇADO; Karina Maria Salvatore de FREITAS; Denis Jardim VILLARINHO (University of São Paulo, 2014)
Objectives: The shape memory resulting from the superelasticity and thermoelastic effect is the main characteristic of thermally activated NiTi archwires and is closely related to the transition temperature range (TTR). The aim of this study was to evaluate the TTR of thermally activated NiTi archwires commercially available. Material and Methods: Seven different brands of 0.019"x0.025" thermally activated nickel-titanium archwires were tested as received by differential scanning calorimetry (DSC) over the temperature range from -100°C to 150°C at 10°C/min. Results: All thermally activated NiTi archwires analyzed presented stage transformation during thermal scanning with final austenitic temperature (Af) ranging from 20.39°C to 45.42°C. Three brands of NiTi archwires presented Af close to the room temperature and, this way, do not present properties of shape memory and pseudoelasticity that are desirable in clinical applications. Conclusions: The thermally activated NiTi archwires present great variability in the TTR and the elastic parameters of each NiTi archwire should be provided by the manufacturers, to allow achievement of the best clinical performance possible.